Performance Differences According to Test Mode and Computer Familiarity on a Practice Graduate Record Exam. - Goldberg, Amie L.; Pedulla, Joseph J. (Educational & Psychological Measurement, 2002)
A study was conducted to investigate the relationships between test mode and computer familiarity with test performance on the Graduate Record Exam. Results indicated that students in the paper-and-pencil group outperformed the computerized-without-editorial control group on all subtests, and that the computerized-with-editorial-control group outperformed the computerized-without-editorial group on the analytical subtest only. It was concluded that the findings highlight the importance of assessing time constraints when converting exams from paper-and-pencil to computer-delivery mode.